Methane Single Cell Protein: Potential to Secure a Global Protein Supply Against Catastrophic Food Shocks - García Martínez, Juan B.; Pearce, Joshua M.; Throup, James; Cates, Jacob; Lackner, Maximilian; Denkenberger, David C. (Frontiers in Bioengineering and Biotechnology, 2022)
Global catastrophes such as a supervolcanic eruption, asteroid impact or nuclear winter could cause global agricultural collapse due to reduced sunlight reaching Earth’s surface. Human civilization’s food production system is unprepared to respond to such events, but methane single cell protein (SCP) could be a key part of the solution. Current preparedness centers around food stockpiling, an excessively expensive solution given that an abrupt sunlight reduction scenario (ASRS) could hamper conventional agriculture for 5 to 10 years. Instead, it is more cost-effective to consider resilient food production techniques requiring little to no sunlight. This study analyses the potential of SCP produced from methane (natural gas and biogas) as a resilient food source for global catastrophic food shocks from ASRS. The following are quantified: global production potential of methane SCP, capital costs, material and energy requirements, ramp-up rates and retail prices. In addition, potential bottlenecks to fast deployment are considered. While providing a more valuable, protein-rich product than alternatives, the production capacity could be slower to ramp up. Based on 24/7 construction of facilities, 7-11% of global protein requirements could be fulfilled at the end of the first year. Despite significant remaining uncertainties, methane SCP shows significant potential to prevent global protein starvation during an ASRS at an affordable price — US$3-5/kg dry.